(untitled) (Development Service Industry Management, 2024)
Social and ethical responsibility is an important factor in the development of tourism institutions, as it contributes to the formation of sustainable relationships between business, society and the environment. One of the key aspects determining the importance of SEV is its positive impact on the reputation of a tourist institution. Consumers choosing travel services increasingly pay attention to the ethics and transparency of the institution’s activities. According to the results of research in recent years, institutions that adhere to the principles of social and ethical responsibility have a higher level of trust and loyalty on the part of customers, which contributes to the growth of their popularity in the market. In addition, social and ethical responsibility increases investment attractiveness, as investors also prefer companies that adhere to ethical standards. That is why a more detailed consideration of the social and ethical responsibility of institutions in the tourism sphere is an actual direction of research in order to increase the level of competitiveness of these institutions and strengthen their positions in the modern, changing market of services. The article examines the components of social and ethical responsibility of tourism institutions and its importance for the sustainable development of the country. The economic, ecological and social components of socio-ethical responsibility are studied. The key aspects of social and ethical responsibility in the context of tourism activities are presented. The profitability of tourism establishments as a factor in the creation and development of social and ethical responsibility has been studied. The relationship between the socio-ethical responsibility of tourism establishments and the Sustainable Development Goals in Ukraine is considered. The interrelationship of various aspects of social and ethical responsibility with specific Sustainable Development Goals is proven, the economic aspect of social and ethical responsibility of tourist establishments of Ukraine is investigated. Challenges to the development of social and ethical responsibility at Ukrainian enterprises are presented. The principles of barrier-freeness and inclusiveness are considered as key components of the social and ethical responsibility of tourism institutions.